2021
DOI: 10.3390/plants10020230
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical and Psychotropic Research of Motherwort (Leonurus cardiaca L.) Modified Dry Extracts

Abstract: The prospect of creating a new medicine with psychotropic activity is shown as a result of studying the chemical composition and pharmacological activity of modified dry extracts of motherwort (Leonurus cardiaca L.) tincture. The most promising substances were the dry extracts, modified by adding small amounts of arginine, valine, phenylalanine, glycine, lysine, and alanine. A total of 15 main phenolic substances were found in the extracts, and eight of them were identified. There were also 10 hydroxycinnamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Modification of bearberry extract with phenylalanine resulted in more pronounced anti-inflammatory and diuretic activity [ 33 ]. Modification of motherwort tincture with different amino acids allowed to create new substances with stress-protective and anxiolytic properties [ 32 ]. Modification of the bilberry leaves extract with amino acid L-arginine allowed to create a substance with significant hypoglycemic and hypolipidemic activity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modification of bearberry extract with phenylalanine resulted in more pronounced anti-inflammatory and diuretic activity [ 33 ]. Modification of motherwort tincture with different amino acids allowed to create new substances with stress-protective and anxiolytic properties [ 32 ]. Modification of the bilberry leaves extract with amino acid L-arginine allowed to create a substance with significant hypoglycemic and hypolipidemic activity [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has become an interesting question, whether the use of such an approach to modify the total plant extract could result in improvement of its biological properties. It was previously shown that the modification of tincture Leonurus cardiaca L. with amino acids has led to the creation of new more active substances with anxiolytic activity [ 32 ]. The modification of the blueberry leaves extract with arginine allowed to create a substance with pronounced hypoglycemic and hypolipidemic activities [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The NIST14 mass spectrum library was used to identify the components. Quantitative determination of the content of substances in the raw material was performed in comparison with a standard sample of menthol [36,37].…”
Section: Methodsmentioning
confidence: 99%
“…The reaction mixture was decanted, and the precipitate was diluted in 1 mL of distilled water; methyl esters of carboxylic acids were extracted with 0.2 mL methylene chloride. The mixture was gently shaken several times within an hour and then the obtained extract of the methyl esters was chromatographed [28,29].…”
Section: Isolation Of Carboxylic Acidsmentioning
confidence: 99%
“…The reaction mixture was decanted, and the precipitate was diluted in 1 mL of distilled water; methyl esters of carboxylic acids were extracted with 0.2 mL methylene chloride. The mixture was gently shaken several times within an hour and then the obtained extract of the methyl esters was chromatographed[28,29].Identification and comparative content determination of carboxylic acidsThe gas chromatography-mass spectrometry (GC-MS) analysis of carboxylic acids was performed on Ag-…”
mentioning
confidence: 99%